STRATEGI KAMPANYE POLITIK KANDIDAT PETAHANA DI DAERAH RENTAN KALAH - Muhamad Erfan; Iis Zilfah Adnan (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
This study discusses a new phenomenon in politics in Garut Regency. Rudy Gunawan and Helmi Budiman (RGHB) became the first incumbent candidates who were successfully re-elected in the second period of regional elections in Garut in 2018. This research is about how candidates and teams in the campaign to win again in areas prone to losing for incumbent candidates. The purpose of this study is to provide an overview, evaluative structure and teamwork in winning the RGHB in the second period. This study uses a qualitative approach. Data was collected through qualitative observations, interviews, and qualitative document collection. The results of this study are incumbent candidates are able to carry out communicator selection strategies, messages supported by the media to strengthen support from old voters Rudy-Helmi during the Regional Head Election in 2013, and change the orientation of choosing from new voters. This research can be used as a concept of political campaign strategy and the winning of political candidates in the future as well as consideration in formulating the incumbent candidate's campaign strategy. Keywords: Campaign; Political Communication; Incumbent